Análise e implementação de um compensador de atrito para válvulas de controle - Castro, Gabriel Barbosa de (2015)
The presence of static friction in control valves generates limit cycles that degrade the performance of control loops in which they operate. Once stiction is detected, its compensation avoids unwanted production stoppages and profit loss until the valve can be corrected. Model-free compensation methods add pulses to the control signal in order to overcome the friction in the actuator. Although those methods are easy to implement and to parameterize as they do not demand complex modeling, eventually they tend to raise valve deterioration due to increased movement caused by the added pulses. This paper analyzes the application of pulses with variable amplitude for stiction compensation in order to reduce the movement of the valve without significant loss of controller performance. Given a maximum specification for the error, a method was proposed to select compensator parameters using operation data. The method was evaluated through different parameter choices simulations, and the result compared to other model-free methods found on literature. The method was implemented in an industrial controller, evaluating its performance under different operating conditions of the control valve and controller. The test results show this method is applicable in a varied array of real situations.